Accessibility disturbances to the biodiversity of urban wetlands due to built environment. (January 2022) - Rojas, Carolina; Sepúlveda, Einer; Jorquera, Felipe; Munizaga, Juan; Pino, Joan
Abstract: Urbanization and urban sprawl in Latin America has led to the social and environmental challenges such as loss and fragmentation of wetland areas, negatively impacting their ecological and social benefits and biodiversity. Urban wetlands are ecosystems that are essential to Latin American cities and are recognized for both their protection against flooding and use as recreational spaces. Additionally, accessibility to urban wetlands can also increase urban residents' well-being. This study analyzes the city model of an urban wetland in the Greater Concepción area (Chile, South America), an area that has recently experienced urban sprawl. First, it identifies the urban fabric and modelling the urban variables of density, distance, roads, and green areas surrounding an inland wetland. Second, it evaluates the accessibility to the wetland and its effect on plant composition using a biodiversity indicator (% native and introduced plants). Literature and social enviroment movements has been showing the Concepción city is growing with no regard for its urban wetland, and its biodiversity is not considered in urban planning. Still, urban wetland remains does have potential benefits for people, species, and possible recreational opportunities. The study contributes to the discussion of the unsustainable spatial model of urbanization interacts with wetland accessibility and with disturbance to biodiversity; the results represent input for urban planning in order to restoring an integrated wetland within cities and improve accessibility by including natural urban wetlands as green infrastructure.